Sport Fans and Online Data Collection: Challenges and Ethics - Brody J. Ruihley; Robin Hardin (Journal of Applied Sports Management, 2014)
The growth of online communities and social networking has provided opportunities to investigate sport fans from a wide range of perspectives. Motivations to consume online media and engage in interactive web functions are areas providing new and innovative research opportunities. There are several ethical considerations when conducting research in an online environment. This article discusses four major ethical values of honesty, responsibility, justice, and beneficence and how each relates to online data collection. Specifically, these four values will guide the discussion focused on issues of intrusion, interaction, and invitation in online communication contexts. Researchers and administrators must consider fans and other stakeholders’ core moral and ethical values in the data collection process.
Keywords: ethics; values; data collection; Internet; social networking